New trends in diagnosing and treating ovarian cancer using nanotechnology - Zhang, Juan; Ding, Haigang; Zhang, Feng; Xu, Yan; Liang, Wenqing; Huang, Liping (Frontiers in Bioengineering and Biotechnology, 2023)
The increased rates of mortality and morbidity around the world are associated with the higher incidence of ovarian cancer. There are numerous histological subtypes of ovarian cancer, each of which has distinct clinical characteristics, risk factors, cell origins, molecular compositions, and therapeutic options. Typically, it is identified at a late stage, and there is no efficient screening method. Standard therapies for newly diagnosed cancer are cytoreductive surgery and platinum-based chemotherapy. The difficulties of traditional therapeutic procedures encourage researchers to search for other approaches, such as nanotechnology. Due to the unique characteristics of matter at the nanoscale, nanomedicine has emerged as a potent tool for creating novel drug carriers that are more effective and have fewer adverse effects than traditional treatments. Nanocarriers including liposomes, dendrimers, polymer nanoparticles, and polymer micelles have unique surface properties in surface chemistry, morphology, and mechanism of action that can distinguish between malignant and normal cells, paving the way for targeted drug delivery. In contrast to their nonfunctionalized counterparts, the development of functionalized nano-formulations with specific ligands permits selective targeting of ovarian cancers and ultimately increases the therapeutic potential. This review focuses on the application of various nanomaterials to the treatment and diagnosis of ovarian cancer, their advantages over conventional treatment methods, and the effective role of controlled drug delivery systems in the therapy of ovarian cancer.